Encrusted Ureteral Stent Retrieval Using Flexible Ureteroscopy with a Ho: YAG Laser - Takashi Kawahara; Hiroki Ito; Hideyuki Terao; Takehiko Ogawa; Hiroji Uemura; Yoshinobu Kubota; Junichi Matsuzaki (Case Reports in Medicine)
A 23-year-old female had bilateral ureteral stents placed due to bilateral renal stones and hydronephrosis. The bilateral ureteral stents were changed every 3 months. A kidney ureter bladder (KUB) film showed left encrustation along the ureteral stent thus necessitating removal; however, the ureteral stent could not be removed cystoscopically. The ureteral stent was, therefore, extracted using flexible ureteroscopy (URS) with a holmium (Ho): yttrium aluminum garnet (YAG) laser.